NÓS - Géo, Daniella; Musea da República, Rio de Janeiro; Cabral, Magali; Santos, Edson; Niklaus, Martha (Rio de Janeiro : Musea da República, 2009)
Piper, Adrian ; Ntakiyica, Aimé ; Geiger, Anna Bella ; Reisewitz, Caio ; Vergara, Carlos ; Benhelima, Charif ; Meireles, Cildo ; Dekyndt, Edith ; Neves, Eustaquio ; Morais, Fabio ; et al.
Musea da República, Rio de Janeiro, 15th of January until 19th of April 2009
kunstcatalogus